“Monetary Targeting Versus Inflation Targeting” - Kadrkhuja, Boboev L; Parvina, Gaybnazarova; Oybek, Utbasarov; Anorakhon , Achilova (Research Parks Publishing LLC, 2022)
In this article you can see to review and analyze modern approaches to monetary targeting and inflation targeting in the world through a deep and comprehensive analysis of the macroeconomic conditions for the implementation of monetary policy at the present stage, to develop proposals for improving these approaches and consider the possibility of using the results obtained in conducting and boosting monetary policy in Uzbekistan. In particular, to adapt foreign achievements to select the most effective mechanisms for the development of the inflation targeting regime in Uzbekistan, the development of measures and the formulation of proposals to ensure the effectiveness of the inflation targeting regime.